Self-harm prevalence and associated factors among street children in Mashhad, North East of Iran - Lida Jarahi; Maliheh Dadgarmoghaddam; Atiyeh Naderi; AmirAli Moodi Ghalibaf (BMC, 2021)
Abstract Background Self-harm is intentional harmful behavior in the context of emotional distress. Street children are boys and girls under eighteen who are forced to work or live on the streets. These children are exposed to violent situations and high-risk behaviors like self-harm. This study investigated the prevalence of self-harm in street children in Mashhad, the second Metropolis of Iran. Methods In this cross-sectional study, 98 children were assessed with a 22-item of self-harm Inventory (SHI) questionnaire. A trained social worker interviewed the participants who were referred to Mashhad Welfare Office, February-July 2020. Results The mean age of participants was 13.8 (2.3) years old, and 71.4 % of them were male. Of street children 59.2 % have had self-harming behavior, among them 8.6 % had one self-harming behavior, and others have more than one. The self-harmed people who had physical injuries, more frequent injuries were hitting (26.5 %), self-starvation (23.5 %), cutting (21.4 %), respectively. In comparison, common psychological injuries were God-distancing (29.6 %) and self-defeating thoughts (19.4 %). The most important risk factors were having a mental disorder (OR = 6.3, P = 0.002), losing parents (OR = 4.4, P = 0.01), self-harming or suicide history in relatives (OR = 3.2, P = 0.001, OR = 4.3, P = 0.03 respectively), low-educated parents (OR = 4.2, P = 002, OR = 2.8, P = 0.02 for father and mother respectively), and age-increasing (OR = 1.5, P = 0.001). Conclusions The prevalence of self-harming in street children is significantly high. Some of these children are in more high-risk conditions that face them to suffer from self-harming at a younger age. Family factors are more important in predicting self-harming and community health decision-makers should provide educational interventions and psychological support for these children and their families.